Eruptive keratoacanthomas associated with dupilumab therapy. (1st February 2022) - Gleeson, D.; Cliff, S.; Das, M.
Abstract: We would like to present the case of eruptive keratoacanthomas associated with dupilumab therapy, which occurred in an 85‐year‐old woman receiving biologic therapy for the treatment of atopic dermatitis. With the increasing prevalence of Dupilumab usage, this is an important potential complication of which clinicians should be aware.